The Weitsman Stoneware Collection at The New York State Museum - J. L. Scherer (The Magazine Antiques, 2002)
Focuses on decorated New York State stoneware received by the New York State Museum in Albany from Adam Joel Weitsman. Weitsman's collection of New York stoneware since the age of eleven; How stoneware was the basic ceramic ware for utilitarian objects in the nineteenth century; Designs on various stoneware pieces, such as flowers and animals; William A. MacQuoid and Co.'s creation of unusual decorations on American stoneware.
Keywords: history